Perancangan Aplikasi Augmented Reality Pembelajaran Agama Islam (Gerakan Dan Bacaan Sholat) Berbasis Android - Puji Pambudi; Dimas Abisono Punkastyo (CV. Multi Kreasi Media, 2024)
Learning can work effectively if all the influential components support each other to achieve the learning objectives. To facilitate teaching and learning activities, especially in learning Islamic Religious Learning teachers should prepare teaching materials to facilitate students understand learning materials. Therefore, it is necessary to develop an appropriate learning media. One of them is Augmented Reality (3D) based media. Augmented Reality (3D) is a real-world application of integration with the virtual world in the form of two-dimensional and three-dimensional projected in a real environment at the same time. The purpose of using Augmented Reality technology in Islamic Religious learning model is expected to assist the teacher in the learning process and also increase the students' interest in joining the learning process. The method used in this study is the research and development method designed by Walter Dick and Lou Carey to produce a particular product. The result of the research is an Augmented Reality application that can run inside android smartphone.